Dyadic emotion regulation in women with borderline personality disorder - Miano, Annemarie; Barnow, Sven; Wagner, Stina; Röpke, Stefan; Dziobek, Isabel (Cognitive therapy and research, 2021)
Emotion regulation (ER) and interpersonal dysfunction constitute key features of borderline personality disorder (BPD). Here, we tested if females with BPD show impairments in dyadic ER, that is in their support seeking and creation of closeness. We investigated if women with BPD might over-rely on their male partner by excessive support seeking and establishing of closeness, during conversations with personally and relationship-threatening topics.